Secukinumab improves the quality‐of‐life of family members and partners of people with psoriasis: Family Dermatology Life Quality Index (FDLQI) results from a randomised open‐label study (SIGNATURE) - A. Y. Finlay; J. N. Barker; A. D. Burden; C. E. M. Griffiths; B. Kirby; M. L. Goodman; C. Neill; R. B. Warren (Wiley, 2022)
Abstract Background The Family Dermatology Life Quality Index (FDLQI) was developed to meet a need for a dermatology‐specific family member/partner quality‐of‐life (QoL) measure. This paper focuses on the analysis and interpretation of FDLQI data (used as an exploratory outcome) collected in the SIGNATURE study. Objectives To measure the impact of secukinumab therapy for moderate to severe plaque psoriasis on the QoL of family members/partners of patients. Methods Randomised, open‐label, non‐comparator study in 53 dermatology centres in the UK and Republic of Ireland. Patients received secukinumab 300 or 150 mg subcutaneously weekly for 4 weeks, then 4‐weekly. FDLQI Results Family members of PASI 75 responders and non‐responders showed improved FDLQI compared to baseline, greater for responders. There was a high level of correlation between FDLQI and Dermatology Life Quality Index (DLQI) scores and positive correlations across all mapped FDLQI and DLQI questions, and a close association between the scales at all timepoints. The estimated FDLQI scores were consistently 56% of those obtained for DLQI. There was an improvement for all FDLQI questions at Week 16 with a mean total score change of 8.2. Most family member subjects had an improved score for all FDLQI questions (75%-91%, Week 12, and 77%-91%, Week 16). Family subjects with a corresponding patient visit DLQI score >10 improved for all FDLQI questions at Week 16 (mean total score change of 5.2). Conclusions Successful therapy for severe psoriasis greatly improved QoL of family members/partners. The FDLQI questionnaire responds well and appropriately to major changes in the disease severity of those affected by plaque psoriasis.